Metodologia inédita para medida da torção ocular reflexa - Barcellos, Ronaldo Boaventura (2001)
Purpose: To develop a methodology to evaluate ocular torsion reflex. Methods: Modifications of a Helmholtz keratometer were made in order to perform keratometry in the primary position and during head tilt (30 degrees to the right, 30 degrees to the left). A total of 16 patients (32 eyes) were examined. There was a mean astigmatism of 0.50 to 3.50 (mean 1.18 ± 0.61). Results: The mean recorded intortions (right eye 5.31 ± 4.23, left eye 5.22 ± 3.91) were slightly lower than the extortions (right eye 7.84 ± 4.79, left eye 7.78 ± 4.09) with no significant difference between both eyes. Conclusions: The modified Helmholtz keratometer allows new and simple method to quantify ocular counterrolling.